(untitled) (Nigerian Dental Journal, 2026)
Background: Dental phobia and previous traumatic treatment experiences are major psychological barriers that drive avoidance and emergency-only dental attendance. Despite being university students, Nigerians frequently delay care due to fears of pain and negative clinical memories. However, research on how these factors specifically impact students’ dental care-seeking habits is currently limited. Objective: This study aims to evaluate the influence of dental phobia and traumatic treatment experiences on dental care-seeking behaviour among students at the University of Ibadan. Methods: A cross-sectional design was utilized, targeting students from non-health-related faculties to minimize professional knowledge bias. A proportionate stratified sampling technique was employed to ensure representation across all faculties. Data were collected using an online self-administered questionnaire comprising sociodemographic characteristics, the Modified Dental Anxiety Scale (MDAS), the Level of Exposure to Distressing Events Questionnaire (LOE-DEQ), and items assessing dental care-seeking behaviour. Analysis included the Chi-square test, Spearman’s rank correlation, and binary logistic regression, performed using SPSS version 27, with statistical significance set at p < 0.05. Results: A total of 397 students were included. The mean age of participants was 22.07 ± 3.13 years. The prevalence of dental phobia and high exposure to traumatic events was 16.9% and 31.8%, respectively. Exposure to traumatic events showed a positive correlation with dental anxiety. Logistic regression revealed that the strongest predictors of dental phobia were a dentist not providing information about an invasive procedure (OR = 3.88), feelings of extreme helplessness during dental treatment (OR = 1.73), and being a victim of a violent crime (OR = 2.40). Individuals with lower levels of exposure were more likely to seek care and attend routine dental check-ups (p < 0.001). Conclusion: Dental phobia and traumatic experiences significantly impede routine dental attendance among University of Ibadan students, with clinical communication failures and personal trauma acting as the strongest predictors of avoidance. Adopting trauma-informed care models that prioritize patient communication and psychological support is essential to mitigate helplessness and improve care-seeking behaviour in this population. Keywords: Dental phobia; Dental anxiety; Care-seeking behavior; Traumatic experiences.